An analysis of two dimensional integral equations of the second kind - M. M. El-Borai; M. A. Abdou; M. Basseem (Le Matematiche, 2007)
In this article, a numerical method is used to solve the two dimensional Fredholm integral equation of the second kind with weak singular kernel using the Toeplitz matrix and product Nystrom method. The numerical results given in this paper are computed using maple 8. The error, in each case, is computed.